A randomized nutrition counseling intervention in pediatric leukemia patients receiving steroids results in reduced caloric intake. Issue 2 (12th September 2016) - Li, Rhea; Donnella, Hayley; Knouse, Phillip; Raber, Margaret; Crawford, Karla; Swartz, Maria C.; Wu, Jimin; Liu, Diane; Chandra, Joya
Abstract: Background: Quality of life in survivors of pediatric acute lymphocytic leukemia (ALL) can be compromised by chronic diseases including increased risk of second cancers, cardiovascular disease, and diabetes. Overweight or obesity further increases these risks. Steroids are a component of chemotherapy for ALL, and weight gain is a common side effect. To impact behaviors associated with weight gain, we conducted a randomized nutrition counseling intervention in ALL patients on treatment. Procedure: ALL patients on a steroid‐based treatment regimen at the MD Anderson Children's Cancer Hospital were recruited and randomized into control or intervention groups. The control group received standard care and nutrition education materials. The intervention group received monthly one‐on‐one nutrition counseling sessions, consisting of a baseline and 12 follow‐up visits. Anthropometrics, dietary intake (3‐day 24‐hr dietary recalls) and oxidative stress measures were collected at baseline, 6 months, and postintervention. Dietary recall data were analyzed using the Nutrition Data System for Research. Results: Twenty‐two patients (median age 11.5 years), all in the maintenance phase of treatment, were recruited. The intervention group (n = 12) reported significantly lower calorie intake from baseline to 12‐month follow‐up and significant changes in glutamic acid and selenium intake ( P < 0.05). Waist circumference was significantly associated with calorie, vitamin E, glutamic acid, and selenium intake. Conclusions: A year‐long dietary intervention was effective at reducing caloric intake in pediatric ALL patients receiving steroid‐based chemotherapy, indicating that this is a modality that can be built upon for obesity prevention and management.